Detection of rat hepatitis E virus in wild Norway rats (Rattus norvegicus) and Black rats (Rattus rattus) from 11 European countries - Ryll, René; Bernstein, Samuel; Heuser, Elisa; Schlegel, Mathias; Dremsek, Paul; Zumpe, Maxi; Wolf, Sandro; Pépin, Michel; Bajomi, Daniel; Müller, Gabi; Heiberg, Ann-Charlotte; Spahr, Carina; et al. (Veterinary microbiology, 2017)
Rat hepatitis E virus (HEV) is genetically only distantly related to hepeviruses found in other mammalian reservoirs and in humans. It was initially detected in Norway rats (Rattus norvegicus) from Germany, and subsequently in rats from Vietnam, the USA, Indonesia, China, Denmark and France. Here, we report on a molecular survey of Norway rats and Black rats (Rattus rattus) from 12 European countries for ratHEV and human pathogenic hepeviruses. RatHEV-specific real-time and conventional RT-PCR investigations revealed the presence of ratHEV in 63 of 508 (12.4%) rats at the majority of sites in 11 of 12 countries. In contrast, a real-time RT-PCR specific for human pathogenic HEV genotypes 1-4 and a nested broad-spectrum (NBS) RT-PCR with subsequent sequence determination did not detect any infections with these genotypes. Only in a single Norway rat from Belgium a rabbit HEV-like genotype 3 sequence was detected. Phylogenetic analysis indicated a clustering of all other novel Norway and Black rat-derived sequences with ratHEV sequences from Europe, the USA and a Black rat-derived sequence from Indonesia within the proposed ratHEV genotype 1. No difference in infection status was detected related to age, sex, rat species or density of human settlements and zoological gardens. In conclusion, our investigation shows a broad geographical distribution of ratHEV in Norway and Black rats from Europe and its presence in all settlement types investigated.
Keywords: Population Density; Genotype 3; Animals; Europe; Female; virus hepatitidy E; ženské pohlaví; druhová specificita; divoká zvířata; lidé; Hepatitis E; Evropa; Species Specificity; hustota populace; Animal Distribution; Black rat; Humans; Phylogeny; Male; Animals, Wild; krysa rodu Rattus; Hepeviridae; zvířata; mužské pohlaví; Norway rat; fylogeneze; rozšíření zvířat; Rats; hepatitida E; Hepatitis E virus